The Role of the United Nations Female Army in Geopolitical Stabilization of the Middle East - Afni Regita Cahyani; Riska Luneto; Muhammad Faizal Alfian; Ahmad Luqman Hakim (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The Middle East is an area that has many geopolitical interests, which has resulted in the emergence of political instability in the region. This has affected the security conditions and the world's political economy. Female peacekeepers are sent by intergovernmental organizations, such as the United Nations (UN), to carry out political stabilization programs in the Middle East. Significant effort has been made by the United Nations to carry out female soldiers’ operations as peacekeepers. This study focuses on the role of female UN soldiers in the geopolitical stabilization efforts in the Middle East. This study uses the concept of the role of inter-governmental organizations (IGO), female military, and geopolitical interests. This research uses a qualitative-explanatory analysis that study the crucial role of female soldiers in IGO's efforts for geopolitical stabilization in the region. This study reveals that female soldiers sent by the UN have a positive contribution to the keeping of peace in the Middle East region.